Breaking Parallel Orientation of Rods via a Dendritic Architecture toward Diverse Supramolecular Structures. (17th July 2019) - Zhang, Ruimeng; Feng, Xueyan; Zhang, Rui; Shan, Wenpeng; Su, Zebin; Mao, Jialin; Wesdemiotis, Chrys; Huang, Jiahao; Yan, Xiao‐Yun; Liu, Tong; Li, Tao; Huang, Mingjun; et al.
Abstract: Self‐assembled nanostructures of rod‐like molecules are commonly limited to nematic or layered smectic structures dominated by the parallel arrangement of the rod‐like components. Distinct self‐assembly behavior of four categories of dendritic rods constructed by placing a tri(hydroxy) group at the apex of dendritic oligo‐fluorenes is observed. Designed hydrogen bonding and dendritic architecture break the parallel arrangement of the rods, resulting in molecules with specific (fan‐like or cone‐like) shapes. While the fan‐shaped molecules tend to form hexagonal packing cylindrical phases, the cone‐shaped molecules could form spherical motifs to pack into various ordered structures, including the Frank–Kasper A15 phase and dodecagonal quasicrystal. This study provides a model system to engineer diverse supramolecular structures by rod‐like molecules and sheds new light into the mechanisms of the formation of unconventional spherical packing structures in soft matter. Abstract : Aufgefächert und umgekegelt : Die bevorzugte parallele Orientierung stäbchenförmiger Moleküle kann durch Synergieeffekte von Wasserstoffbrücken und dendritischen Architekturen gebrochen werden. Die resultierende molekulare Form (fächer‐ oder kegelartig) mit ausgeglichener Enthalpie und Entropie reguliert die Bildung verschiedener supramolekularer Strukturen mit gekrümmten Grenzflächen.